2015
DOI: 10.1103/physrevd.92.113011
|View full text |Cite
|
Sign up to set email alerts
|

Model-independent determination of the axial mass parameter in quasielastic antineutrino-nucleon scattering

Abstract: Understanding the charged current quasielestic (CCQE) neutrino-nucleus interaction is important for precision studies of neutrino oscillations. The theoretical description of the interaction depends on the combination of a nuclear model with the knowledge of form factors. While the former has received considerable attention, the latter, in particular the axial form factor, is implemented using the historical dipole model. Instead, we use a model-independent approach, presented in a previous study, to analyze t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
(111 reference statements)
4
25
0
Order By: Relevance
“…However, from a theoretical point of view, it has been indicated that this ansatz is not a good choice, e.g. see [81,82]. For example, a recent analysis of G A [83], using conformal mapping or z-expansion, shows that the dipole ansatz systematically underestimates the uncertainty of AFF.…”
Section: Experimental Datamentioning
confidence: 99%
“…However, from a theoretical point of view, it has been indicated that this ansatz is not a good choice, e.g. see [81,82]. For example, a recent analysis of G A [83], using conformal mapping or z-expansion, shows that the dipole ansatz systematically underestimates the uncertainty of AFF.…”
Section: Experimental Datamentioning
confidence: 99%
“…Furthermore, modifications in the nuclear medium are also studied in Refs. [92][93][94][95][96][97].…”
Section: Introductionmentioning
confidence: 99%
“…[16,17], and several applications are found in Refs. [15,[18][19][20]. Related formalism and applications may be found in [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Form Factor Nonlinearitiesmentioning
confidence: 99%
“…19 At the nucleon-level, the basic signal process for neutrino detection is charged-current quasielastic scattering, ν � n → � − p. Figure 14 illustrates that with proper treatment of form factor shape, the nucleonlevel uncertainty on the cross section is an order of magnitude larger than previously thought. 20 This complicates the program of constraining nuclear effects from measurement: for example, in Fig.14, 19 Another recent application is to the study of photon initiated processes at the LHC [93]. 20 Reference [95] 2 .…”
Section: Nucleon Form Factors For Neutrinos and Other Processesmentioning
confidence: 99%
See 1 more Smart Citation